Optimization of Glucose Recovery from Saccharomyces cerevisiae Waste via Hydrolysis Using RSM - Ubaidillah Bramantyo Esnandhik; Fatimah Azzahra; Ni Ketut Sari (G-Tech: Jurnal Teknologi Terapan, 2025)
The liquid waste resulting from the regeneration of Saccharomyces cerevisiae contains a significant amount of starch, which has the potential to be optimized for glucose production. This study aims to optimize glucose levels from the liquid waste using hydrolysis with the Response Surface Methodology (RSM). The tested variables include the volume of Saccharomyces cerevisiae regeneration liquid waste (mL): 300; 600; 900; 1200; and 1500, as well as water volume (mL): 200; 400; 600; 800; and 1000. RSM with a Central Composite Design (CCD) requires 13 experimental data combinations of variables. The hydrolysis results were analyzed using RSM to determine the effect of variables and their interactions on glucose content. Optimization of glucose levels using RSM resulted in an optimal glucose content of 23.5% at a liquid waste volume of 1378.79 mL and a water volume of 1.5238 mL, based on an analysis using Minitab 19 software. Glucose content testing from 25 data points showed the highest level at 27% for a liquid waste volume of 900 mL and a water volume of 600 mL, while spectrophotometry recorded a peak glucose content of 29.7% under the same variables. The findings of this study can be the basis for developing a more efficient hydrolysis process that produces glucose which can help industry to make waste processing methods more efficient and increase the added value of by-products.